Performance modeling and analysis of TCP and UDP flows over software defined networks. (15th March 2019) - Lai, Yuan-Cheng; Ali, Ahsan; Hossain, Md. Shohrab; Lin, Ying-Dar
Abstract: Software Defined Networking (SDN) decouples the control plane from the data plane, thereby facilitating network virtualization, dynamic programmability and flexibility in network management. Previous studies on SDN modeling focus only on packet-level arrivals. However, if flow-level arrivals are not also considered, the model cannot properly reflect the true probability of packets being sent to the controller. Accordingly, the present study proposes two analytical models for predicting the performance of TCP and UDP flows over SDN, respectively, given the assumption of both flow-level arrivals and packet-level arrivals. In constructing the models, the switch and controller are considered jointly and four-dimensional states are used to evaluate the steady-state probabilities of the states. Analytical formulae are derived for the average packet delay and packet loss probability of the TCP and UDP flows. Simulation results very well match with the analytical ones, thereby validating our analytical models. The results show that TCP significantly outperforms UDP over SDN architectures. In particular, TCP reduces the packet delay by 12 ∽ 50% and the packet loss probability by 25 ∽ 100%.